Formulation of a legal framework for a comprehensive protection of human trafficking victims in Malaysia - Ab Hamid, Zuraini (2018)
Human trafficking victims have been criminalised and denied their rights in Malaysia, where they are misidentified as perpetrators and their needs for proper shelter, medical assistant, and safe environment are repudiated. The introduction of UN Protocol 2001 marks a significant effort to support their rights. Although Malaysia is not a signatory to the protocol, as a UN member, it is committed to comply with the protocol. The support is strengthened with the implementation of Anti-Trafficking in Persons and Smuggling of Migrants Act 2007 and National Action Plan 2010-2015 and 2016-2020. These are vital because Malaysia is graded by Trafficking in Persons report for its achievement in combatting human trafficking. Thus far, Malaysia has not properly fulfilled the enforcement mechanism and it is not positioned in Tier 1 of the TIP report, of which its main objective is to propose a systematic enforcement mechanism as required under the international and domestic legal frameworks.